KONSEP MAHABAH DALAM PERSPEKTIF TAFSIR MAUDHU’I - Samud Samud (UIN Siber Syekh Nurjati Cirebon, 2017)
Mahabah, is in Arabic Mahabbah derived from the word ahabba-yuhibbu-mahabbatan, which in language means deep love, love, or deep love. The Mahabah is defined as